Job Matching and Coalition Formation with Utility or Disutility of Co-workers - Jinpeng Ma (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
This paper studies the job matching market in Kelso and Crawford(1982) with one exception that co-workers may generate utility or disutility in the workplace. We provide a simple idea to show how a great number of sufficient condiions for a nonempty core in the literature can be extended to this labor market. We also provide a deterministic and a stochatic recursive dynamic system each of which converges to an efficient core outcome as long as the core is nonempty.
Keywords: D71; 330